Hubungan Antara Pola Makan dan Aktivitas Fisik Terhadap Tingkat Depresi di Masa Pandemi Pada Pelajar SMAN 1 Manyar Gresik, Indonesia: Correlation Between Dietary Patterns and Physical Activity Towards Depression Level During Pandemic Among Students of SMAN 1 Manyar Gresik, Indonesia - Annisa Citra Herrastri Hertanto; Ancah Caesarina Novi Marchianti; Muhammad Hasan (Amerta Nutrition, 2023)
Background: Unhealthy dietary patterns and low physical activity during a pandemic can be risk factors for depression. Objectives: This study aimed to analyze the correlation between dietary patterns and physical activities toward depression levels during the pandemic among SMA N 1 Manyar Gresik students. Methods: This research used observational with a cross-sectional study design at SMA N 1 Manyar Gresik. The sample was 78 students from the 12th grade. The sampling technique used was simple random sampling. The data obtained were then analyzed using the Kendall Correlation test to determine the correlation between dietary patterns and physical activities on the depression level. Each variable was obtained by analyzing the Food Frequency Questionnaire, Food Recall 2x24 hours, International Physical Activity Questionnaire-Short Form, and Modified Beck Depression Inventory-II. Results: The results showed relationships between diet and depression levels. Diet was assessed from the frequency of the type of food that dominated in the last month and macronutrient intake. There were relationships between the frequency of food consumption that dominated in the last month and the depression level (p=0,003; r=0,319) and between macronutrient intake and depression level. Conclusions: The results showed the need to increase food consumption from the minimally processed foods group by paying attention to macronutrient intake and performing physical activity in moderate to high-intensity categories according to the recommendations of the adolescent age group to prevent depression.